Pemodelan Perencanaan Roda Gigi Lurus - Hendri Budiman; Muhamad Kamil (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
Gear is important element in transmission systems. By using gear, transmission power more efficient thanother transmission like as belt etc. In gear design needed mathematic equation complicatedly and long time. Thepaper covered modeling gears design. The modeling can be simple gears design, especially linear gear. Thesoftware make in prototype stage. By using software hoped the gears design faster and accurately.Keywords: gear, modeling, gears design, software.